Implementation of SSP (Subject-Specific Pedagogy) Based on TPACK for Students' Scientific Literacy Skills - F. Shoufika Hilyana; Fina Fakhriyah; Siti Masfuah; Nordin Mamat (Jurnal Pemberdayaan Masyarakat, 2026)
This study aims to examine the effect of implementing Subject-Specific Pedagogy (SSP) based on the Technological Pedagogical Content Knowledge (TPACK) framework on students' scientific literacy skills in science learning. The study employed a quantitative experimental design with a one-group pre-test–post-test. The participants were students from the Elementary Teacher Education Program at Universitas Muria Kudus, selected using a simple random sampling technique. Data were collected using a scientific literacy test covering scientific knowledge, scientific competence, and contextual understanding. The data were analyzed using descriptive statistics, normalized gain (N-gain), and a paired sample t-test. The results showed that students' scientific literacy skills increased significantly after the implementation of a TPACK-based SSP, as indicated by an improvement in the average score from the medium category in the pre-test to the very high category in the post-test, with an N-gain in the moderate category and a statistically significant difference between pre-test and post-test scores. These findings indicate that integrating pedagogy, content, and technology through TPACK-based SSP effectively enhances students' scientific literacy. This study contributes to science education by providing empirical evidence that a TPACK-based SSP can be an effective instructional approach to strengthen scientific literacy among pre-service elementary school teachers and to support the development of science learning aligned with the demands of the digital era.